O homem duplicado: o narrador na obra de José Saramago - Pereira, Cinthia Evandro Martins (2024)
This master's dissertation aims to study the narrator in the work The duplicate man, with the aim of investigating from the analysis of the work together with the statements of the author, José Saramago, about what is a narrator. These assertions are related to the Marxist Theory in order for the writer to adhere to this current of thought. Authors such as Antonio Gramsci, Eça de Queiroz, Georg Lukács, Karl Marx, Leandro Konder and Octavio Ianni base the text on the sociology of literature and Marxist theory. Michel Foucault, Mikhail Bakhtin, Roland Barthes and Walter Benjamin appear under the aspects of the genre novel, author, narrator and character. Comparative literature dialogue with the study of two films with themes similar to the plot and the characters of the work, being the film adaptation of the book The Duplicate Man and the film Stranger than fiction in conjunction with Dostoyevsky's book, The Double. The investigation of the work is done by means of passages that prove the relations between the literary theory and the author's affirmation that he is present in his works, as well as the comparisons between the elements of the narrative of the novel with the theoretical texts. The question of whether the author is in the literary text is proved by means of the analysis of the work, which the author's voice together with the narrator transforms the narration beyond the omniscience, presenting a mixture between the voices of the narrator and the characters with the constant use of the 1st person of the plural and the intrusions and dialogues of the Narrator with the reader.